معايير تدويل عقود التجارة الدولية - تجيني, عبد القادر (unuversity of eloued- جامعة الوادي, 2022)
ملخص: أثار أمر تكييف عقود التجارة الدولية جدلا بين الفقهاء، فتعددت المعايير المتبعة من أجل الحكم على دولية العقد من عدمه. فأصحاب المعيار القانوني يرون أنه يكفي لإطلاق الصفة الدولية على العقد مجرد اتصال عناصره القانونية بأكثر من نظام قانوني واحد. حاليا تم هجر المعيار الأول واللجوء إلى النظرية الموضوعية لاعتبار العقد التجاري عقدا دوليا، فتم بذلك الاعتماد على المعيار الاقتصادي، فالعديد من العقود التجارية تتجاوز حدود البلد وتؤثر على المصالح التجارية الدولية دون أن يكون أحد عناصرها أجنبيا. فإذا اتصل العقد بمصالح تلك التجارة كان دوليا، بصرف النظر عن مدى توافر العناصر القانونية الأخرى، طالما كان ذلك الاتصال فعالا ومؤثرا. الكلمات المفتاحية: التجارة؛ الدولية؛ المعيار؛ الاقتصادي؛ القانوني؛ Abstract: The issue of adapting international trade contracts has sparked controversy among jurists. This raised concerns to create standards in order to judge the internationality of these contracts. The proponents of legal standards believe that it is sufficient to make the contract international merely when connecting its legal elements to more than one legal system. Currently, the first standard has been abandoned and the objective theory is adopted instead for the internationalization of international trade contracts. Thus, relying on the economic standard has been resorted to, as many trade contracts go beyond the borders of the country and affect international commercial interests without considering any of its elements as being outlandish. If the contract is tied with the interests of that trade, then it is internation al regardless of the availability of other legal elements, as long as that contact is effective and influential. key words: trade; international; standard; economic; legal.
Standards for the Internationalization of International Trade Contracts
مقال
Keywords: التجارة ; الدولية ; المعيار ; الاقتصادي ; القانوني; trade ; international ; standard ; economic ; legal